2023
DOI: 10.48550/arxiv.2301.00799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moiré alchemy: artificial atoms, Wigner molecules, and emergent Kagome lattice

Abstract: Semiconductor moiré superlattices comprise an array of artificial atoms and provide a highly tunable platform for exploring novel electronic phases. We introduce a theoretical framework for studying moiré quantum matter that treats intra-moiré-atom interactions exactly and is controlled in the limit of large moiré period. We reveal an abundance of new physics arising from strong electron interactions when there are multiple electrons within a moiré unit cell. In particular, at filling factor n = 3, the Coulomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…We thus demonstrated that SBMFT is an excellent approach to narrow down a large parameter space to regions that can potentially host spin-liquid ground states on extended kagome lattice models, without the need to immediately resort to numerically more expensive methods. This might be of great use especially in the rapidly evolving understanding of the microscopic description of TMD moiré bilayers [99,100].…”
Section: Discussionmentioning
confidence: 99%
“…We thus demonstrated that SBMFT is an excellent approach to narrow down a large parameter space to regions that can potentially host spin-liquid ground states on extended kagome lattice models, without the need to immediately resort to numerically more expensive methods. This might be of great use especially in the rapidly evolving understanding of the microscopic description of TMD moiré bilayers [99,100].…”
Section: Discussionmentioning
confidence: 99%
“…This simplified description succeeds in describing several phenomena including incompressible states at fractional fillings known as generalized Wigner crystals. However, as we showed recently, this approach inevitably fails at large moiré period where Coulomb interaction necessarily exceeds the band gap [64].…”
mentioning
confidence: 89%
“…In Ref [64], it was shown that the continuum model Hamiltonian can be characterized by three important length scales: 1) the moiré lattice constant a M , 2) the quantum confinement length ξ 0 ≡ 2 /(mk)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that holes for 𝜈 > 1 fill a charge transfer band 28 , which can again be described by a t-J model with an enhanced hopping through the physics of Zhang and Rice 39 . An alternative possible explanation is electron-assisted hopping due to Coulomb repulsion within a moiré site that effectively increases the size of the localized orbital and therefore the hopping integral 40 .…”
Section: Main Textmentioning
confidence: 99%